ANALISIS MOTIVASI BELAJAR MATEMATIKA SISWA MAN 1 KOTA CIREBON PADA PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 - Azizah Azizah; Putik Rustika; Desy Lusiyana (Department of Mathematics Education, Universitas Kuningan, 2022)
This study aims to determine the students' motivation to learn mathematics in online learning during the covid-19 pandemic at MAN 1 Cirebon City in class XI. This type of research is a field research with a descriptive qualitative approach. Methods of data collection is done by observation, questionnaires, interviews and documentation. Researchers took high school students at MAN 1 Cirebon City class XI as a sample, data source sample collection was done purposively and snowball to produce a sample that can logically be considered representative of the population and find key informants who have a lot of information. The results of the study stated that the mathematics learning motivation of MAN 1 Cirebon City students during the covid-19 pandemic was in the